Many Roads to Mecca: The Controversy of Safarwadi Cave Pilgrimage in the Local Muslims - Mokhtar, Wan Khairul Aiman Wan; Dewi, Subkhani Kusuma; Masri, Muhammed Sahrin bin Haji; Baharun, Hasan; Fawaid, Achmad (Yayasan Irwan Abdullah Cendekia, 2024)
The pilgrimage activities performed by local Muslims in the Safarwadi cave are considered to have a similar function and value as the Hajj pilgrimage activities conducted directly in the city of Mecca. However, this phenomenon is typically excluded from scientific discussions. This study addresses deficiencies in previous research by examining the characteristics, meanings, and community responses to pilgrimage activities performed at Safarwadi cave. This descriptive qualitative study, based on a case study approach, resulted in three significant findings. Firstly, the pilgrimage activities performed by local Muslims at Safarwadi cave have a different set of practices and symbols than those observed in the Hajj activities conducted in the city of Mecca. Secondly, the pilgrimage activities performed at Safarwadi Cave are considered by local Muslims to have the same function and value as the Hajj activities conducted in the city of Mecca. Thirdly, the community’s response to pilgrimage activities performed by local Muslims at Safarwadi cave is considered to be an unbelievable, irrational, and abnormal pilgrimage activity. This study also recommends that in-depth interviews should be conducted to gain a deeper understanding of the pilgrimage activities performed by local Muslims.